Kinetic modeling, optimization of biomass and astaxanthin production in Spirogyra sp. under nitrogen and phosphorus deficiency - Nadia Delfi Zafira; Malvin Yulius Christian Pakpahan; I Putu Ikrar Satyadharma; Khairul Hadi Burhan; Erly Marwani (Indonesian Journal of Biotechnology, 2023)
This study studied the optimum nitrogen (N) and phosphorus (P) concentrations for biomass and astaxanthin production in Spirogyra sp. Spirogyra sp. was cultivated in Blue Green (BG) medium with N/P concentrations adjusted to 1.1/0.01; 1.1/0.03; 1.1/06; 1.1/0.09; 2.2/0.01; 2.2/0.03; 2.2/0.06; 2.2/0.09; 4.4/0.01; 4.4/0.03; 4.4/0.06; 4.4/0.09, 6.6/0.01; 6.6/0.03; 6.6/0.06 and 6.6/0.09 mM. The results showed an increase in biomass accumulation for lower concen‐ trations of N and N:P ratio with the highest accumulation at N/P 1.1/0.03 mM, i.e. 485 mgdryweight and a growth rate of 0.22 d‐1. Astaxanthin accumulation was also found to increase, with the highest at N/P 1.1/0.01 mM, i.e. 0.269 mg/gdryweight, on the 12th day of cultivation. Based on biomass and astaxanthin accumulation, the highest astaxanthin productivity was 0.07 μg/cm2/d at N/P concentration 1.1/0.09 mM. Kinetic models were developed using the Haldane and Luedeking–Piret equations. The growth and astaxanthin production parameters obtained were μmax 0.18±0.02 d‐1, kN 68.2 ± 24.2 mg/L, ki 301.8 ± 78.5 mg/L, YN 0.93 ± 0.68 gbiomass/nitrate, α 0.36 ± 0.69, β ‐0.01 ± 0.02, and kA 0.04 ± 0.03, thus indicating that a lower N concentration is suitable for the cultivation of Spirogyra sp. In conclusion, Spirogyra sp. should be cultivated under nitrogen deficiency for continuous astaxanthin production.